Analisis Tata Ruang Kantor Dinas Pendidikan Provinsi Jambi - Hidayah, Nurul Hidayah; Firman, Firman; Muspawi, Mohamad (Indonesian Educational Administration and Leadership Journal (IDEAL), 2024)
The aim of this research is to find out and describe how office layout is implemented in the Jambi provincial education office. The aim of this research is to find out and describe how office layout is implemented in the Jambi provincial education office. Office layout is the determination of space requirements and practical use of factors deemed necessary for carrying out office work at a reasonable cost. Meanwhile, work efficiency is the correct way to carry out something without wasting time, energy and money. Ability to carry out tasks well and precisely without wasting energy and money.